Pseudomonas spp. beneficial in agriculture - Sánchez Carrillo, Román; Guerra Ramírez, Priscila (Revista Mexicana de Ciencias Agrícolas, 2022)
Bacteria of the genus Pseudomonas inhabit a wide variety of environments, which is a reflection of their diverse metabolic capacity, this has allowed them to adapt to variable environmental conditions, also, this genus is considered ambivalent due to the fact that some species establish beneficial relationships with plants and others pathogenic relationships with plants, animals and humans. In the present work, we focus on the positive impact that this bacterial genus has in the agricultural field, due to its capacity as a plant growth-promoting bacterium (PGPB), being one of the best options as a plant and soil inoculant, to improve plant growth and disease management, through the wide range of metabolites that the beneficial strains are capable of producing, bacteria of this genus have been identified with diazotrophic capacity, producing antibiotics, auxins, siderophores, cellulolytic enzymes, organic acids for phosphorus solubilization and promotion of induced systemic resistance against phytopathogens, which makes them ideal in agricultural production either for biocontrol or biofertilization, likewise, their use does not affect the environment or the health of farmers.